2020
DOI: 10.21873/anticanres.14561
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Linear Energy Transfer Affect Cell-killing and Radiosensitizing Effects of Spread-out Carbon-ion Beams

Abstract: Background/Aim: The cell-killing and radiosensitizing effects of carbon-ion (C-ion) beams with low linear energy transfer (LET) are underexplored. We aimed to demonstrate the cell-killing effects of 60 Co gamma rays and Cion beams at various LET values and the radiosensitizing effect of C-ion beams at various LET and cisplatin levels. Materials and Methods: Human uterine cervical cancer cells were irradiated with 60 Co gamma rays and C-ion beams at different levels of LET, with and without cisplatin treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In an in vitro study, Shiba et al. reported a difference in survival rate with varying LET in CIRT of HeLa cells in human cervical adenocarcinoma [ 40 ]. Furthermore, the passive and scanning methods may result in slight differences in LET due to the different methods of forming the dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, Shiba et al. reported a difference in survival rate with varying LET in CIRT of HeLa cells in human cervical adenocarcinoma [ 40 ]. Furthermore, the passive and scanning methods may result in slight differences in LET due to the different methods of forming the dose distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the importance of different LET values on radiosensitizing effects with cisplatin has been investigated. Shiba et al found that low-LET carbon-ion irradiation in combination with cisplatin produced higher cytotoxic effects than high-LET carbon-ion irradiation in cervical cancer cells [34]. On the other hand, carbon ion irradiation combined with cisplatin showed superior potential to kill breast cancer cells with irreparable DNA damage [35].…”
Section: Discussionmentioning
confidence: 99%
“…C) G2/M phase cell distribution following treatment with 2.0 Gy carbon ion-beams with 0.5 μg/ml gemcitabine and 6.0 Gy photon beams with 0.5 μg/ml gemcitabine. cells and the chemotherapeutic agent cisplatin a dependence of radiosensitization on the linear energy transfer (LET) of carbon ion irradiation, showing an increase in radiosensitivity in the low LET range (18). This could be attributed to the ability of high-LET irradiation to overcome radioresistance.…”
Section: Discussionmentioning
confidence: 99%